TEMPORAL ETHICS AND THE PARADOX OF SCIENTIFIC RESPONSIBILITY IN CHRISTOPHER NOLAN’S TENET - Anti, Upi; Rosalinah, Yanti (Universitas Islam Sumatera Utara (UISU), 2025)
Amid growing concerns over the ethical risks of accelerating technological development, this study examines how Christopher Nolan’s Tenet confronts the tensions of temporal ethics and scientific responsibility through a narrative and visual design that functions as a critical reflection on time, agency, and moral consequence. Using a qualitative interpretive design, the study employs film-textual analysis based on Knight’s methodological framework and Strano’s concept of the “ludic space,” while grounding its ethical argument in Hans Jonas’s ethic of responsibility. Data were generated through repeated close-viewing of temporally inverted sequences and interpretive mapping of narrative causality. The analysis yields three central findings: Tenet transforms determinism into an ethical condition where human agency persists within inevitability; the film reconfigures Hans Jonas’s ethic of responsibility by inverting its direction from present-to-future obligation to future-to-present retaliation driven by ecological trauma; and the cognitive struggle of the spectator to comprehend the film’s nonlinear story world represents an ethical act in itself, simulating the characters’ moral dilemmas under temporal uncertainty. The finding is not merely a science fiction narrative but a critical philosophical allegory for contemporary moral responsibility, challenging the direction, burden, and mandate of technological power across time.